Oceanographic investigations within the framework of II stage of the State Program of Ukraine researches in Antarctica - Artamonov, Yu. V. (Ukrainian Antarctic Journal, 2010)
In the work the main results of oceanographic researches, obtaining within the framework II-stage (2002-2008) of the State Program of Ukraine researches in Antarctica, are presented. It is noted that on this stage in default of marine expeditions main attention was focused the carrying out of researches on the basis of modern archives of hydrometeorological information. From these data the seasonal variability of SST linear trends and cross-correlation between the Southern oscillation index (SOI) and SST anomalies in the South hemisphere are investigated. On the basis of the satellite and contact SST measurements the scheme of South ocean fronts is specified, the regularity of their seasonal cycle and feature of interannual variability are discovered. The results of the accompanying hydrometeorological measurements, carrying out CEV “Academic Fedorov” on the program of International Polar Year 2007-2008, are generalized. The seasonal and interannual variability of sea ices of different closeness and cross-correlation between variability of sea ices closeness, air temperature in the Antarctic peninsula region and atmospheric circulation indexes are investigated.